HUBUNGAN KONSUMSI AIR MINUM DENGAN KELUHAN SUBJEKTIF AKIBAT TEKANAN PANAS PADA PEKERJA PANDAI BESI DI DESA BANTARAN PROBOLINGGO - Raga Aditya Hidayat (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyze the relationship between water consumtion with subjective symptoms as an effect of heat stress among blacksmith. Methods:This study was an observational research with cross sectional design. The respondent of this study was 16 blacksmith workers in the Bantaran village, Bantaran District, Probolinggo. The Data of this study were collected using questionnaires and observations. Variables that used in this study were drinking water consumption, as independent variable, and subjective symptoms as dependent variable. This study used Spearman correlation test to determine the correlation between the consumption of drinking water with subjective symptom due to heat stress. Results: This study showed that 68.8% of respondents consumed water with amount less than the recommendation, 87.5% of respondents drank water with a frequency more than or equal to 16 times per day and the drinking water locations were in the affordable place for the respondent. All of respondents consumed water during work. The symptoms that always perceived was excessive sweating and severe thirsty. The Spearman correlation test results indicated a correlation between the quantity of drinking water with subjective symptoms due to heat stress (r = −0.615, p=0.011). Furthermore, there was also a relationship between the frequency of drinking with subjective symptoms caused due to heat stress (r = −0.512, p=0.043). Conclusion: The conclusion of this study was there is a relationship between the consumption of drinking water with subjective symptoms due to heat stress, especially the quantity of drinking water and the frequency of drinking. Therefore, it is recommended to blacksmith workers in the village of Bantaran, District Bantaran, Probolinggo to consumed drinking water with the amount of 250 ml every 30 minutes during work.